16.67% Rigid and 14.06% Flexible Organic Solar Cells Enabled by Ternary Heterojunction Strategy. Issue 39 (14th August 2019) - Yan, Tingting; Song, Wei; Huang, Jiaming; Peng, Ruixiang; Huang, Like; Ge, Ziyi
Abstract: Ternary heterojunction strategies appear to be an efficient approach to improve the efficiency of organic solar cells (OSCs) through harvesting more sunlight. Ternary OSCs are fabricated by employing wide bandgap polymer donor (PM6), narrow bandgap nonfullerene acceptor (Y6), and PC71 BM as the third component to tune the light absorption and morphologies of the blend films. A record power conversion efficiency (PCE) of 16.67% (certified as 16.0%) on rigid substrate is achieved in an optimized PM6:Y6:PC71 BM blend ratio of 1:1:0.2. The introduction of PC71 BM endows the blend with enhanced absorption in the range of 300–500 nm and optimises interpenetrating morphologies to promote photogenerated charge dissociation and extraction. More importantly, a PCE of 14.06% for flexible ITO‐free ternary OSCs is obtained based on this ternary heterojunction system, which is the highest PCE reported for flexible state‐of‐the‐art OSCs. A very promising ternary heterojunction strategy to develop highly efficient rigid and flexible OSCs is presented. Abstract : High efficiencies of 16.67% (certified as 16.0%) for rigid and 14.06% for flexible organic solar cells (OSCs) are achieved by employing a PM6:Y6:PC71 BM ternary system. This is a promising ternary heterojunction strategy for the development of highly efficient rigid and flexible OSCs.